Law enforcement within the framework of peace support operations - Arnold, Roberta, 1974- (International and comparative criminal law series., 2008)
Addresses the general question whether law enforcement shall be a Peace Support Operations (PSO) task. This book addresses the limits and possibilities of law enforcement by PSO. It also focuses instead on law enforcement within PSO, illustrating problems related to the prosecution of members of PSO forces suspected of illegal activities.